Genotype-phenotype correlation for pulmonary function in cystic fibrosis. Issue 7 (1st July 2005) - de Gracia, J; Mata, F; Álvarez, A; Casals, T; Gatner, S; Vendrell, M; de la Rosa, D; Guarner, L; Hermosilla, E
Abstract : Background: Since the CFTR gene was cloned, more than 1000 mutations have been identified. To date, a clear relationship has not been established between genotype and the progression of lung damage. A study was undertaken of the relationship between genotype, progression of lung disease, and survival in adult patients with cystic fibrosis (CF). Methods: A prospective cohort of adult patients with CF and two CFTR mutations followed up in an adult cystic fibrosis unit was analysed. Patients were classified according to functional effects of classes of CFTR mutations and were grouped based on the CFTR molecular position on the epithelial cell surface (I–II/I–II, I–II/III–V). Spirometric values, progression of lung disease, probability of survival, and clinical characteristics were analysed between groups. Results: Seventy four patients were included in the study. Patients with genotype I–II/I–II had significantly lower current spirometric values (p<0.001), greater loss of pulmonary function (p<0.04), a higher proportion of end-stage lung disease (p<0.001), a higher risk of suffering from moderate to severe lung disease (odds ratio 7.12 (95% CI 1.3 to 40.5)) and a lower probability of survival than patients with genotype I–II/III, I–II/IV and I–II/V (p<0.001). Conclusions: The presence of class I or II mutations on both chromosomes is associated with worse respiratory disease and a lower probability of survival.